Epitope-Blocking Enzyme-Linked Immunosorbent Assay To Differentiate West Nile Virus from Japanese Encephalitis Virus Infections in Equine Sera - Kitai, Yoko (American Society for Microbiology, 2007)
West Nile virus (WNV) is now widely distributed worldwide, except in most areas of Asia where Japanese encephalitis virus (JEV) is distributed. Considering the movement and migration of reservoir birds, there is concern that WNV may be introduced in Asian countries. Although manuals and guidelines for serological tests have been created in Japan in preparedness for the introduction of WNV, differential diagnosis between WNV and JEV may be complicated by antigenic cross-reactivities between these flaviviruses. Here, we generated a monoclonal antibody specific for the nonstructural protein 1 (NS1) of WNV and established an epitope-blocking enzyme-linked immunosorbent assay that can differentiate WNV from JEV infections in horse sera. Under conditions well suited for our assay system, samples collected from 95 horses in Japan (regarded as negative for WNV antibodies), including those collected from horses naturally infected with JEV, showed a mean inhibition value of 8.2% and a standard deviation (SD) of 6.5%. However, inhibition values obtained with serum used as a positive control (obtained after 28 days from a horse experimentally infected with WNV) in nine separate experiments showed a mean of 54.4% and an SD of 7.1%. We tentatively determined 27.6% (mean + 3 × SD obtained with 95 negative samples) as the cutoff value to differentiate positive from negative samples. Under this criterion, two horses experimentally infected with WNV were diagnosed as positive at 12 and 14 days, respectively, after infection.